Mobile health applications for quality healthcare delivery - Moumtzoglou, Anastasius, 1959- (Advances in healthcare information systems and administration (AHISA) book series, 2019)
"This book explores the emergence of mHealth in healthcare settings. It focuses on the broad range of technologies available and looks at the effects of mHealth on the industry and stakeholders. It also examines the infrastructure and architecture needed to support these technologies and discusses the the impact of mHealth on existing technologies"--Provided by publisher.